2020
DOI: 10.1093/jee/toaa079
|View full text |Cite
|
Sign up to set email alerts
|

Baseline Plant-to-Plant Larval Movement of Spodoptera eridania in Bt and Non-Bt Soybean and Its Possible Impacts on IRM

Abstract: The widespread use of transgenic technologies has led to the emergence of insect populations resistant to Bt toxins. Some lepidopteran pest species also appear to naturally have some level of tolerance to certain proteins, such as some species of Spodoptera to Cry1Ac. One of the main strategies to manage resistance is the use of refuge areas, the success of which is in part dependent on larval movement of the target pest. Thus, in order to assess the viability of a refuge strategy addressing Spodoptera eridani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…In Brazil, C. includens larvae were observed to prefer to position themselves predominantly in the lower and mid region of the soybean plants, 48 less exposed to insecticide, while the capacity of A. gemmatalis to move longer distances in the canopy may expose it more readily to treatment. Moreover, larval movement behavior and the difference in distance moved between the species emphasizes the importance of understanding on‐plant movement 49 , 50 and plant‐to‐plant movement of lepidopterans 51–53 . The movement of larvae in a seed mixture refuge strategy system, for example, might expose the insect to sublethal doses of Bt proteins by feeding on plant tissues of differential Bt protein content, or by initial feeding on a Bt plant and subsequent feeding on a non‐ Bt plant, and vice versa , so larval mortality may not be achieved 54 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, C. includens larvae were observed to prefer to position themselves predominantly in the lower and mid region of the soybean plants, 48 less exposed to insecticide, while the capacity of A. gemmatalis to move longer distances in the canopy may expose it more readily to treatment. Moreover, larval movement behavior and the difference in distance moved between the species emphasizes the importance of understanding on‐plant movement 49 , 50 and plant‐to‐plant movement of lepidopterans 51–53 . The movement of larvae in a seed mixture refuge strategy system, for example, might expose the insect to sublethal doses of Bt proteins by feeding on plant tissues of differential Bt protein content, or by initial feeding on a Bt plant and subsequent feeding on a non‐ Bt plant, and vice versa , so larval mortality may not be achieved 54 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, larval movement behavior and the difference in distance moved between the species emphasizes the importance of understanding on-plant movement 49,50 and plant-to-plant movement of lepidopterans. [51][52][53] The movement of larvae in a seed mixture refuge strategy system, for example, might expose the insect to sublethal doses of Bt proteins by feeding on plant tissues of differential Bt protein content, or by initial feeding on a Bt plant and subsequent feeding on a non-Bt plant, and vice versa, so larval mortality may not be achieved. 54 Thus, the widespread release and adoption of Bt crops and the issues involving the different refuge models reinforce the necessity for further research to evaluate the effect of larval mobility and behavior on these strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, movement of this species appears to be nondirectional and independent 28 ; however, especially under eld conditions, it could be in uenced by biotic or abiotic factors. In a similar study with Spodoptera eridania Stoll (Lepidoptera: Noctuidae) larvae, it was also observed that the species move in all directions independent of the season or cultivar 14 . Pannuti et al 2016 assessing S. frugiperda and S. albicosta movement observed a dispersal governed by nondirectional sensory information of both species; however, S. frugiperda remained nearer the release point, presented a more aggregated and symmetrical distribution.…”
Section: Discussionmentioning
confidence: 74%
“…The infestation was performed by xing infested lea ets from the rearing cages to the upper surface of a central plant lea et with a small piece of adhesive tape, taking care so that the neonates did not stick to the tape. This technique reduced stress to the neonates, resulting in e cient transfer of the neonates to the infested plant 14 . The eld infestation occurred at dusk to reduce stress to the larvae and maximize the effectiveness of the infestation.…”
Section: Plant-to-plant Larval Movementmentioning
confidence: 99%
See 1 more Smart Citation